Potential the biological or chemical control of lettuce white rot and maintain productivity - Samuel Allah; Ahmed Abou El-Yazeid; hany gamal; ahmed bondok (Arab Universities Journal of Agricultural Sciences, 2020)
The experiments were executed on the autumn and the winter of (2016 /2017, 2017/2018) seasons at Qalyub area, EL-Qalyubia governorate, Egypt. The main objective for this study to find out the efficacy of several biological and the chemical controls on growth and productivity of lettuce crop and management on white rot disease caused on Sclerotinia sclerotiorum. Thus, four treatments were applied as follow 1- the control (water application),2- Trichoderma asperellum, 3-Salicylic acid and 4- Calcium Chloride, which were evaluated and compared for the three fungicide as follow : 1- Iprodione , 2- Tebuconazole with Fluopyram and 3-Tebuconazole at the doses (85 & 100 ; 200 &100 and 50 &100 g or ml / 100L-1 respect.) . Which they tested for their ability for increasing the lettuce crop productivity and suppress mycelial growth of S. sclerotiorum pathogen by treatments were sprayed on two times on plants at (15-19 BBCH) stages by using backpack sprayer by 250 L./Fed.). Results indicated that, Iprodione applications significantly gave the highest indications of total and the Marketable yield in compared with the other experimental treatments for both seasons. Moreover, the two times of sprayes by Iprodione and Salicylic acid treatments had significantly lowered the disease incidence and disease severity and increasing the control efficiency in the both seasons. Whereas, the other treatments, Tebuconazole with Fluopyram or Tebuconazole and Trichoderma asperellum had a moderate effecacy on the lettuce crop productivety or the disease severity and incidence of Sclerotinia sclerotiorum in compared to the control treatment. In the contrast, application by Calcium Chloride had a low effect on the average yield or final yield as a mass and marketable plant in the both seasons and had insignificant effect on the disease severity or incidence of S. sclerotiorum despite low to medium recovery following applications. Finally, the control treatment was the lowest.